In vitro and in vivo effects of palm kernel cake oligosaccharides on Salmonella enterica serovar enteritidis infection - Foo, Rui Qing (2021)
Non-digestible oligosaccharides (NDOs) have been reported to possess prebiotic and immunomodulatory properties. With the European Union (EU) wide ban on the use of antibiotic growth promoters (AGP) in the livestock industry, the search for AGP alternatives to maintain livestock productivity is highly sought after. Previous studies have shown that NDOs from palm kernel cake (PKC), a by-product of the palm oil industry were able to confer a protective effect against Salmonella colonization in young chickens. Being young vertebrae with an immature immune system, they would have to rely on the strength of their innate immune responses to prevent Salmonella infection. Therefore the objective of this study was to investigate the ability of NDOs from PKC to affect the innate immune response in a Salmonella enterica serovar (ser.) Enteritidis (S. Enteritidis) infection model utilizing in vitro and in vivo approaches. The in vitro approach consisted of an anti-adherence assay using Caco-2 cells, a Salmonella killing assay using U-937 macrophages and a lactate dehydrogenase (LDH) assay to monitor cellular damage. The in vivo approached utilized zebrafish larvae to observe the effects of NDOs from PKC on lipopolysaccharide (LPS) induced nitric oxide (NO) levels, S. Enteritidis colonization patterns and its effect on zebrafish’s gene expression. The results of the in vitro study revealed that the NDOs fraction from PKC with a lower degree of polymerization (DP), termed ‘Small’ (DP ≤ 6), was better than the NDOs fraction from PKC with a larger DP, termed ‘Big’ (DP > 6), at significantly (p ≤ 0.05) reducing S. Enteritidis adherence to Caco-2 epithelial cells. Both Small and Big fractions were comparable to one another at increasing the rate of Salmonella killing in U-937 macrophages. In terms of reducing cellular damage, both the Small and Big were capable of significantly reducing cellular damage in Caco-2 cells although the Small fraction showed a stronger correlation between decreasing S. Enteritidis numbers and cellular damage in U-937 macrophages than the Big fraction. When compared to commercial NDOs fructooligosaccharide (FOS) and mannanoligosaccharide (MOS), both the Small and Big fraction were found to be comparable, if not better than MOS and FOS at reducing S. Enteritidis adherence, increasing S. Enteritidis elimination and reducing cellular damage in vitro. As the Small fraction was better than Big, it was chosen for subsequent in vivo studies and renamed ‘OligoPKC’. The results of the in vivo study showed that OligoPKC was comparable to the commercial NDOs at reducing LPS induced NO levels in zebrafishes but showed a significant increase in S. Enteritidis colonization within the gastrointestinal tract at 24 hours postinfection when compared to the infected control. This might stem from a weaker upregulation of myeloperoxidase (MPX) expression when compared to other infected groups. In conclusion, NDOs from PKC were able to affect the innate immune response in a S. Enteritidis infection model in vitro and in vivo but care should be taken when selecting the appropriate animal infection model and interpreting its results.